Efficiency of the use for doubled haploids in onion breeding (Allium cepa L.) - E. A. Cherednichenko; V. F. Pivovarov; S. F. Gavrish; A. F. Pershin; M. V. Budylin (Овощи России)
Relevance. In onion breeding, quickly obtain aligned material is an urgent target for create parent forms of heterosis hybrids. Using classical methods with helping of backcrosses, this is achieved in 10-12 years. Using the technology of doubled haploids, it is possible to reduce these terms several times, and also to avoid the manifestation of inbred depression when obtaining lines by self-pollination. At the same time, the most effective in the production of haploids is the use of whole flower buds as an explant, unlike ovules and ovaries, the production of which is more time-consuming and labor-intensive.Methods. The doubled onion haploids were obtained by the method of ovule culture on the basis of the biotechnology laboratory of the Gavrish Breeding Center using the technology that based on the methodological recommendations of Monakhos S.G. et al., 2014. DH–onion plants with a developed root system and leaf apparatus were planted in the open ground and grown according to the technology generally accepted for the zone at the sites of the Gavrish breeding center, Krymsk, Krasnodar Territory. The obtained commercial bulbs were evaluated according to the RTG/46/2 method.Results. It was obtain doubled haploids, which were tested for ploidness by flow cytometry. 40 digaploid onion plants have been created. As a result of further development after transplantation into the open ground, storage, springization and selection, 3 uterine bulbs were obtained for further reproduction and inclusion in the breeding process.